Borrowing within Malayic; The role of exotericity - Gil, David (Wacana, Journal of the Humanities of Indonesia, 2024)
This paper presents a general survey of borrowing within the Malayic language family, in which both the source and the recipient languages are either varieties of Malay/Indonesian, or other closely-related Malayic languages. The survey provides empirical evidence for a generalization governing the directionality of borrowing, specifying that the donor variety tends to be higher than the recipient variety on a scale of exotericity, making reference to a set of features of a broadly sociolinguistic nature. In terms of a sociolinguistically-based typology of Malayic varieties, the most frequent instances of borrowing within Malayic are from Standard Malay and Indonesian into koiné varieties and traditional dialects, as well as from koiné varieties into traditional dialects.